Magnetic nanobraids of iron-doped amorphous silica - Yu, M. B. (2011)
Using silicon, iron oxide, and graphite powders as source materials, braid-like nanostructures of iron-doped amorphous silica were fabricated by vapor-phase transport. Each braid was composed of a bunch of entangled nanowires with uniform size. The formation of the nanobraids was mainly due to simultaneous nucleation in a vapor–liquid–solid process. Magnetic measurement showed that the iron-doped silica nanobraids were ferromagnetic at room temperature.